Assessment of antioxidant capacity and cytotoxicity of selected Malaysian plants - Ling, L.T.; Radhakrishnan, A.K.; Subramaniam, T.; Cheng, H.M.; Palanisamy, U.D. (2010)
Thirteen Malaysian plants; Artocarpus champeden, Azadirachta indica, Fragaria x ananassa, Garcinia mangostana, Lawsonia inermis, Mangifera indica, Nephelium lappaceum, Nephelium mutobile, Peltophorum pterocarpum, Psidium guajava and Syzygium aqueum, selected for their use in traditional medicine, were subjected to a variety of assays. Antioxidant capability, total phenolic content, elemental composition, as well as it cytotoxity to several cell lines of the aqueous and ethanolic extracts from different parts of these selected Malaysian plants were determined. In general, the ethanolic extracts were better free radical scavengers than the aqueous extracts and some of the tested extracts were even more potent than a commercial grape seed preparation. Similar results were seen in the lipid peroxidation inhibition studies. Our findings also showed a strong correlation of antioxidant activity with the total phenolic content. These extracts when tested for its heavy metals content, were found to be below permissible value for nutraceutical application. In addition, most of the extracts were found not cytotoxic to 3T3 and 4T1 cells at concentrations as high as 100 mu g/mL. We conclude that although traditionally these plants are used in the aqueous form, its commercial preparation could be achieved using ethanol since a high total phenolic content and antioxidant activity is associated with this method of preparation.